2020
DOI: 10.1093/cid/ciaa1496
|View full text |Cite|
|
Sign up to set email alerts
|

Severe Coronavirus Disease 2019 (COVID-19) is Associated With Elevated Serum Immunoglobulin (Ig) A and Antiphospholipid IgA Antibodies

Abstract: Background Severe coronavirus disease 2019 (COVID-19) frequently entails complications that bear similarities to autoimmune diseases. To date, there is little data on possible IgA-mediated autoimmune responses. Here, we aim to determine whether COVID-19 is associated with a vigorous total IgA response and if IgA antibodies are associated with complications of severe illness. Since thrombotic events are frequent in severe COVID-19 and resemble hypercoagulation of antiphospholipid syndrome (APS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 33 publications
5
55
1
Order By: Relevance
“…However, we failed to find any difference when blood samples were stratified for time since the onset of symptoms. The same evidence has been highlighted in the studies conducted by Huang and collegues and Hasan Ali and collegues where a higher IgA response was observed in critical and more sever patients [34,35].…”
Section: Discussionsupporting
confidence: 73%
“…However, we failed to find any difference when blood samples were stratified for time since the onset of symptoms. The same evidence has been highlighted in the studies conducted by Huang and collegues and Hasan Ali and collegues where a higher IgA response was observed in critical and more sever patients [34,35].…”
Section: Discussionsupporting
confidence: 73%
“…As demonstrated in Table 2, the presence of antiphospholipid antibodies (aPL) has been observed in COVID-19 patients around the world (18)(19)(20)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). The association between aPL and disease severity was shown in three studies (39,54,56), but not in another study (46). Lupus anticoagulant and non-criteria IgA anti-β2glycoprotein-I/anticardiolipin antibodies (57) were the most prevalent aPL, with the prevalence of 3-92, 0-37, and 0-32% in patients with moderate to severe disease ( Figure 2).…”
Section: Antiphospholipid Antibody Syndrome (Aps)mentioning
confidence: 98%
“…The B-cell response is also likely dysregulated, although reports are inconsistent, confounded by methodological issues surrounding the detection of antigen-specific immunoglobulins ( 166 , 167 ) and whether systemic (circulatory) or local (particularly mucosal) responses were assessed ( 168 ). For example, enhanced secretory mucosal IgA responses, detected in the circulation in severe COVID-19, were hypothesised to confer damaging effects via induction of inflammatory cytokines ( 169 171 ); although IgA levels in saliva from COVID-19 patients showed only a moderate correlation with COVID-19 severity ( 172 ) and other studies found no difference with disease severity ( 155 ). Circulating IgG levels were higher in patients with severe COVID-19, which has been hypothesised to promote macrophage hyper-inflammatory responses ( 173 ); although the effect of viral load on the secretion of antibodies has not been ruled out.…”
Section: Overview Of Immune Response To Sars-cov-2 Infectionmentioning
confidence: 99%